Analisis UU No. 23 Tahun 2006 terhadap Pelayanan Pencatatan Kelahiran Oleh Pemerintahan Desa: Implementasi, Tantangan, dan Faktor Pendukung - Saliro, Sri Sudono; Tamrin, Tamrin; Eny Kurnia; Mintarsih, Endah; Evametha Vitranilla, Yudith (WELFARE STATE Jurnal Hukum, 2025)
The village government has a responsibility to encourage the community to be orderly in administration, one of which is orderly in making birth certificates. This study aims to analyze the implementation of birth registration services in the village government, and to reveal the supporting and inhibiting factors in the implementation of these services. The results of the study found that the implementation of birth registration services in the jurisdiction of Sambas Regency is not only carried out by the Population and Civil Registry Office but can also be carried out by the village and sub-district governments. Services are carried out online through the SIAK and PELAKAT applications of the Sambas Population and Civil Registry Office. Supporting factors for birth registration services are the existence of clear legal regulations, human resource factors, and facilities and infrastructure factors. While the inhibiting factors are the lack of public awareness and participation, other obstacles that are not smooth internet networks and PELAKAT or SIAK applications that are under maintenance, so that it will have an impact on the length of time to complete birth registration documents.